On Exploration of Benefits Behind Successful Adoption of RPA in Finance, Banking and Investment Banking - Jauhar, Jyotin; Aggarwal , Remica (Contemporary Research in Business, Management and Economics Vol. 9, 2024)
Nowadays, switching to automation software opens many opportunities and enhances the workflow for all accountants and financial personnel. This research work discusses various benefits banks can gain from adopting automation as well as robotic process automation in banking, finance and investment banking. It thereafter studies the hierarchical interwoven linkages amongst these factors through the VAXO technique of Interpretive Structural Modeling Methodology [ISM].